KEANEKARAGAMAN JAMUR MAKROSKOPIS DI KAWASAN AIR TERJUN CURUG EMBUN KOTA LUBUKLINGGAU - Erni Afrita; Ria Dwi Jayati; Reny Dwi Riastuti (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aims to determine the types, diversity index, species evenness index, dominance index, and relative density of macroscopic fungi in the Waterfall area of ​​Curug Embun, Marga Bakti Village, North Lubuklinggau District I. This research is quantitative descriptive. Data collection techniques in this study using the roaming method with sampling using purposive sampling technique. The results of the analysis of the macroscopic fungal diversity index in the Curug Embun Waterfall area were 1.3530, the species evenness index was 0.4516, the dominance index was 0.4776 and the highest relative density was 68.027%. There are 3 edible species and 17 non-edible mushrooms. 17 species of macroscopic mushrooms in the Waterfall area of ​​Curug Embun were found. The diversity index, dominance, and Simpson index are in the medium category. Schizophyllum commune is the most commonly found species.